Numerical solutions for thermal and solutal transport of Jeffrey fluid flow subject to rotation via Keller–Box method - Sarfraz, Mahnoor; Muhammad, Khursheed (Multiscale and Multidisciplinary Modeling, Experiments and Design, 2025)
This research analyzes the heat and mass transfer of electrically conducting Jeffrey fluid flow over a spiraling disk. Employing the Jeffrey fluid model, the rheology of the system is studied with Joule heating, heat source/sink, thermal radiation, rotation, and chemical reaction. The fluid interacts with the disk in an anticlockwise rotation and radial stretching generates a stable laminar stagnation flow. This investigation has broad implications for industries such as polymer manufacturing and chemical engineering, where enhancing process efficiency and product quality is paramount. The solutions of the problem are numerically solved via Keller-Box method. The investigation examines the effects of pertinent parameters on fluid velocity, temperature, concentration, skin drag, Nusselt number and Sherwood number. The results are presented in graphical and tabular forms. It is seen that lowering relaxation-to-retardation ratio reduces radial and azimuthal velocity and temperature by weakening elastic recoil, resistance to deformation and enhance viscous dissipation. Surface rotation decreases radial velocity through centripetal effects and increases azimuthal velocity. Increment in radiation parameter increases temperature and thermal distribution rate due to stronger radiative heat transfer.